Implementation of Magnetoelectric Dipoles in Metasurfaces for 5G Applications - Xuexuan Ruan; Kai Wang; Qinyu Zhang (IEEE Open Journal of Antennas and Propagation, 2022)
The well-known magnetoelectric dipole (ME-dipole) has huge adoption in antenna designs. In this paper, we manage to implement ME-dipoles in metasurfaces. The unit cell of an ME-dipole metasurface consists of a cross slot etched on the middle metal layer and an ME-dipole loaded on each side of the middle metal layer. The unit cell of an ME-dipole metasurface is designed based on the antenna theory, i.e., one ME-dipole works as a receiving antenna while the other ME-dipole works as a transmitting antenna. The metasurface is then formed by arraying these unit cells in a periodic grid with optimal cell size. Three ME-dipole metasurfaces, including a frequency selective surface (FSS), a polarizer, and a transmitarray, are presented to show the potential of the proposed metasurface design method. The proposed concept and the design method are validated using simulation as well as experiments.